Analisis Naratif Komunikasi Interpersonal Ayah dan Anak Dalam Film - Ananti, Rina Ayu; Wardhana, Ardiyanto (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
The lack of effective communication between father and child can trigger conflicts and misunderstandings in family relationships, as represented in the film Scandal Makers produced by MD Pictures. This study aims to analyze interpersonal communication between father and child in the film Scandal Makers, produced by MD Pictures in 2023. The research employs a qualitative approach using narrative analysis based on Tzvetan Todorov's model, which divides narrative structure into three main parts: initial equilibrium, conflict disruption, and resolution. This approach is used to explore the patterns of interpersonal communication between father and child in the film Scandal Makers by MD Pictures (2023). Data was collected through content observation and document analysis, focusing on scenes depicting interactions between the father (Oscar) and the child (Karin). The tools used include dialogue transcripts and video player applications. Data analysis was conducted in three stages: identifying narrative structure, interpreting elements of interpersonal communication, and drawing conclusions. The findings reveal that Scandal Makers portrays the dynamics of interpersonal communication between father (Oscar) and child (Karin) through three narrative stages: initial equilibrium, conflict disruption, and resolution, in line with Tzvetan Todorov's theory. The conflict in the story is triggered by ineffective communication caused by Oscar's ego and fear of losing his reputation. However, through reflection and the courage to be open with each other, their relationship is restored, and trust is rebuilt. This study emphasizes that effective communication is crucial in resolving family conflicts. The film not only serves as entertainment but also conveys a moral message about the importance of openness, empathy, and acceptance in building harmonious family relationships.